Tax Administration in Small Economies. (Technical Notes and Manuals; Technical Notes and Manuals ;, 2010)
This technical note analyzes tax administration in small economies. Choosing the right organization structure is a key component of any program of tax administration reform and modernization. It creates a solid platform from which all other enhancements can follow. Organizations and agencies involved in providing advice to governments on modern tax administration have developed principles that should drive decisions on organization structure. This note describes the general principles of tax administration organization. Characteristics of tax administration in small and microeconomies are also elaborated.